Introduction to Bioinformatics - Teresa K Attwood (Pearson Education / Dorling kindersley ( India) Pvt.Ltd., 2007)
Bioinformatics, the application of computers in the biological sciences, especially analysis of biological sequence data, is becoming an essential tool in molecular biology as genome projects generate vast quantities of data.